Inflammation aggravated the hepatotoxicity of triptolide by oxidative stress, lipid metabolism disorder, autophagy, and apoptosis in zebrafish - Li, Chenqinyao; Zhang, Changqing; Zhu, Chengyue; Zhang, Jie; Xia, Qing; Liu, Kechun; Zhang, Yun (Frontiers in Pharmacology, 2022)
Triptolide is a major compound isolated from the Tripterygium wilfordii Hook that is mainly used for the treatment of autoimmune disorders and inflammatory diseases. Though triptolide-induced hepatotoxicity has been widely reported, the hepatic effects when the patients are in an inflammatory state are not clear. In this study, we used low-dose Lipopolysaccharides (LPS) to disrupt the inflammation homeostasis in the liver of zebrafish and explored the hepatotoxicity of triptolide under an inflammatory state. Compared with the Triptolide group, LPS-Triptolide cotreatment execrates the liver injury with a remarkable increase of liver size and decrease of liver-specific fluorescence intensity, accompanied by significant elevation of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activities. Liver cell damages were further demonstrated by histological staining and scanning electron microscopy observation. Lipid metabolism was severely impaired as indicated by delayed yolk sac absorption, accumulated triglycerides in the liver, and dysregulation of the related genes, such as ppar-α, cpt-1, mgst, srebf1/2, and fasn. Oxidative stress could be involved in the molecular mechanism as the Nrf2/keap1 antioxidant pathways were down-regulated when the zebrafish in an inflammatory state. Moreover, the expression of autophagy-related genes such as beclin, atg5, map1lc3b, and atg3 was also dysregulated. Finally, apoptosis was significantly induced in responses to LPS-Triptolide co-treatment. We speculate that triptolide could exacerbate the immune response and impair lipid metabolism, resulting in enhanced sensitivity of the zebrafish liver to triptolide-induced toxic effects through disruption of the antioxidant system and induction of apoptosis.